1994
DOI: 10.1002/1097-0142(19940915)74:6<1720::aid-cncr2820740613>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

bcl-2 expression in epidermal keratinocytic diseases

Abstract: Background. The bcl‐2 protein has been shown to suppress apoptosis, and overexpression of the bcl‐2 protein has been reported in several malignant tumors. Skin is one of the largest organs in the body, and the most common human malignancies arise from keratinocytes in the epidermis. In this paper, the authors analyzed immunohistochemically the expression of the bcl‐2 protein in several keratinocytic (KC) tumors and inflammatory skin disorders to investigate the role of bcl‐2 in the development of benign and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
4
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 15 publications
9
66
4
1
Order By: Relevance
“…We agree with Waring et al (1996) that multiple differences exist between KAs and SCCs, and that the existence of 'metastasizing KAs' is not absolutely convincing (Krunic et al, 1996). On the other hand, focal loss of Dsg staining in AKs is similar to that observed in SCCs (Krunic et al, 1996) and, together with bcl-2 positivity (Nakagawa et al, 1994) as well as high FAL (Rehman et al, 1994, underlines the premalignant nature of this neoplasm. However, this does not explain the long-term low incidence of invasive growth and the 20% regression rate observed in this neoplasm (Marks et al, 1988;Schwartz, 1996).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We agree with Waring et al (1996) that multiple differences exist between KAs and SCCs, and that the existence of 'metastasizing KAs' is not absolutely convincing (Krunic et al, 1996). On the other hand, focal loss of Dsg staining in AKs is similar to that observed in SCCs (Krunic et al, 1996) and, together with bcl-2 positivity (Nakagawa et al, 1994) as well as high FAL (Rehman et al, 1994, underlines the premalignant nature of this neoplasm. However, this does not explain the long-term low incidence of invasive growth and the 20% regression rate observed in this neoplasm (Marks et al, 1988;Schwartz, 1996).…”
Section: Discussionsupporting
confidence: 70%
“…In the process of maturation the bcl-2 activity disappears, consistent with the initiation of apoptosis at involution of KAs. Bcl-2 positivity was also detected in hypertrophic AKs and was confined to the atypical keratinocytes (Nakagawa et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…In general, the data obtained in the present study are in agreement with those of several other authors who evaluated the expression of PCNA, p53, bax and bcl-2 in addition to other proteins related to cell proliferation and apoptosis in oral lichen planus (21,26,(29)(30)(31)(32). For these authors, the alterations in the expression of these proteins were a strong indicator of the potential for malignant transformation of oral lichen planus, as these proteins participate actively in oral carcinogenesis.…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, the pattern of expression of Bcl-2 protein in normal skin remains controversial. In fact, we found lack of keratinocyte Bcl-2 positivity as previously reported by some authors (27)(28), but our results are not consistent with findings of other authors, who demonstrated Bcl-2 immunoreactivity in normal basal keratinocytes (12,29). The expression of Bax protein, which is the product of a protooncogene of the Bcl-2 family acting as death agonist (30), has also been investigated, giving negative findings.…”
Section: Pi: Steven-johnson Syndrome (Sjs) Versus Healthy Skin (Hs) Psupporting
confidence: 54%